Religious Persecution in Sub-Saharan Africa: Jihadism and ICC Prosecution - Quirós-Fons, Antonio (Religions, 2022)
The most intense violations of religious freedom have been recently perpetrated in Asia, by governments, and in Africa, by jihadist terrorists linked to intercommunal violence, especially in the Sub-Saharan region. This work focuses on African countries where states have failed to manage the threats to the most fundamental human rights, posed by terrorist groups on religious terms. It analyzes whether and how those atrocities perpetrated by both al-Qaeda and the Islamic State, and their associates, can be prosecuted by the International Criminal Court. For this purpose, the Al Mahdi case constitutes an exceptional precedent regarding jurisdiction, accountability, and judgement.